2014
DOI: 10.1099/ijs.0.067199-0
|View full text |Cite
|
Sign up to set email alerts
|

Brevundimonas denitrificans sp. nov., a denitrifying bacterium isolated from deep subseafloor sediment

Abstract: A novel Gram-stain-negative, aerobic, heterotrophic, stalked and capsulated bacterium with potential denitrification ability, designated strain TAR-002 T , was isolated from deep seafloor sediment in Japan. Colonies lacked lustre, and were viscous and translucent white. The ranges of temperature, pH and salt concentration for growth were 8-30 6C, pH 6.0-10.0 and 1-3 % (w/v) NaCl. Phylogenetic analysis based on 16S rRNA gene sequences confirmed that strain TAR-002 T belongs to the genus Brevundimonas of the cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 47 publications
1
19
0
Order By: Relevance
“…All deep-sea isolates identified in this study are represented in the classification of operational taxonomic units from pyrosequencing results [76] and corresponded to genera that were previously reported in marine sediments [55,70,[77][78][79][80][81]. The fact that isolates retrieved from selective cultures of MV sediments are associated with the degradation of PHs is consistent with previous findings, in which communities from inactive MVs presented a preference for degradation of PAHs, instead of simpler PHs [76].…”
Section: Isolation and Identification Of Isolatessupporting
confidence: 88%
“…All deep-sea isolates identified in this study are represented in the classification of operational taxonomic units from pyrosequencing results [76] and corresponded to genera that were previously reported in marine sediments [55,70,[77][78][79][80][81]. The fact that isolates retrieved from selective cultures of MV sediments are associated with the degradation of PHs is consistent with previous findings, in which communities from inactive MVs presented a preference for degradation of PAHs, instead of simpler PHs [76].…”
Section: Isolation and Identification Of Isolatessupporting
confidence: 88%
“…By contrast, Acinetobacter relative abundance was below 1% in fish fed the FM and TB0.1 diets, while Brevundimonas was the predominant genera. Brevundimonas strains are usually been isolated from soil (Yoon, Kang, Oh, Lee, & Oh, 2006), sand (Yoon et al, 2006) and sub-seafloor sediment (Tsubouchi et al, 2014), but rarely from infections (Estrela & Abraham, 2010). These changes in predominant or 'core' microbiota induced by tributyrin supplementation may provide evidence for the improvement of intestine health.…”
Section: Discussionmentioning
confidence: 99%
“…The ER method is a powerful tool to eliminate unnecessary microbiota and obtain rare environmental microorganisms by potential application of optimal wave shape, optimal resonance frequency, optimal amplitude, and optimal time length. We reduced unwanted microbiota and isolated the novel gram-negative strain Brevundimonas denifitricans from 1180-m deep-seafloor sediment 11 m below the seabed off the Shimokita Peninsula, Japan, using the ER method (Tsubouchi et al 2014 ). We reported that microorganisms such as E. coli recognized and selectively attached to small regions of a −0.4-V vs. Ag/AgCl applied potential 5-μmϕ circular ITO microelectrode array at the single-cell level (Koyama et al 2013 ).…”
Section: Discussionmentioning
confidence: 99%